Communication and Filipino seamen's wives imagined communion and the intimacy of absence - Galam, Roderick G. (Philippine studies : historical and ethnographic viewpoints, 2012)
"Seamen's wives know absence very well. Their lives are striated by it. Based on interviews with seamen's wives conducted in Ilocos Norte, this article investigates the communicative practices obtaining amid absence and separation, and the wives' activities that bring their husbands home and bring "home" to their husbands. It examines how new communication technologies, particularly the cellphone, have engendered new ways of becoming present and intimate. For seamen's families, cellphone-mediated intimacy creates a space of imagined communion, which becomes the locus of the reproduction of family and effective ties and is itself the result of these emotional and material activities."